Dani Karavan : Retrospektive ; ["Dani Karavan - Retrospektive", 14. März - 1. Juni 2008, Martin-Gropius-Bau Berlin, Ausstellung] - Karavan, Dani 1930-2021 Ill; Jacobi, Fritz Andreas 1944-; Jacobi, Fritz Hrsg; Berliner Festspiele; Martin-Gropius-Bau; Nationalgalerie; Muzeʾon Tel Aviv; Ausstellung Dani Karavan, Retrospektive (Wasmuth, 2008)
Ausstellungskatalog